2018
DOI: 10.1111/ceo.13138
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of optic nerve photography for glaucoma screening: a review

Abstract: Visual evaluation of the optic nerve has been one of the earliest and most widely used methods to evaluate patients for glaucoma. Photography has proven very useful for documentation of the nerve's appearance at a given time, allowing more detailed scrutiny then, and later comparison for change. Photography serves as the basis for real-time or non-simultaneous review in telemedicine and screening events allowing fundus and optic nerve evaluation by experts elsewhere. Expert evaluation of disc photographs has s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 64 publications
1
38
0
Order By: Relevance
“…In the present study, the PPV for fundus photography with two or more glaucomatous optic features in the detection of glaucoma was 83.9% (78/93), consistent with previous reports that the overall accuracy of non‐mydriatic fundus photography for the detection of glaucoma in diabetic patients was about 80% . Availability of portable devices create opportunities for practical and affordable glaucoma screening in underserved regions by non‐physicians . Recent advances in artificial intelligence algorithms and telemedicine models also offer the promise of more rapid and accurate evaluation of optic nerve photographs in a large populations, potentially further improving access to glaucoma care .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, the PPV for fundus photography with two or more glaucomatous optic features in the detection of glaucoma was 83.9% (78/93), consistent with previous reports that the overall accuracy of non‐mydriatic fundus photography for the detection of glaucoma in diabetic patients was about 80% . Availability of portable devices create opportunities for practical and affordable glaucoma screening in underserved regions by non‐physicians . Recent advances in artificial intelligence algorithms and telemedicine models also offer the promise of more rapid and accurate evaluation of optic nerve photographs in a large populations, potentially further improving access to glaucoma care .…”
Section: Discussionsupporting
confidence: 90%
“…25 Availability of portable devices create opportunities for practical and affordable glaucoma screening in underserved regions by non-physicians. 26 Recent advances in artificial intelligence algorithms Healthcare system perspective was used for the cost assessment. All costs are in US dollars at the average 2016 exchange rate (1 US dollar = 6.64 RMB) and changed into 2019 cost using an inflation rate of 2% base on the 2016-2019 Consumer Price Index of China.…”
Section: Discussionmentioning
confidence: 99%
“…However, on those original ODPs, a large percentage (142/600, 23.7%) of images was misdiagnosed by the ophthalmologists. This might have been owed to the fact that, even with high-resolution, good-quality ODPs, there is often limited detectability of small and indistinct pathologies due to insufficient time, fatigue, and/or lack of experience [7]. We demonstrated that by use of enhanced ODPs, detection accuracy for ONH pathology can be greatly improved.…”
Section: Plos Onementioning
confidence: 94%
“…In real clinical practice, limited patient cooperation, small pupils, or media opacities can limit the performance of ODP [7]. As a result, ODPs can have several limitations, such as insufficient resolution, low color contrast, and inconsistency of image quality (especially in cases of media opacity due to cataracts).…”
Section: Introductionmentioning
confidence: 99%
“…Optic disc photography remains the fundamental approach in glaucoma screening [8,9]. Disc photography reviewed by experienced specialists can achieve similar diagnostic performance as that of advanced imaging technology such as optical coherence tomography (OCT) [10], and combining other modalities with fundus images did not necessarily increase the diagnostic power in teleglaucoma [7].…”
Section: Introductionmentioning
confidence: 99%